THE PRESPA AGREEMENT, ETHNICITY AND NATIONALITY (Annual of the Faculty of Philosophy in Skopje, 2019)
The Prespa Agreement (PA) between Athens and Skopje was meant to be afinal solution to the ‘name issue’. Yet the dispute has never been only about the statename, which is proved by the 20-pages long text. A plethora of other provisions is tobe implemented erga omnes (internationally and domestically). Despite the insistenceof the external mediators that the name dispute has never concerned the issuesof ethnicity, nationality, culture, and language, these issues indeed appear to be simultaneouslycentral as well as the Achilles heel of the deal. This paper does not dealwith conceptual and theoretical aspects of ethnicity and nationality; yet its focus ison the fact that the Agreement indeed regulates identity issues; i.e. it represents a legalintervention in spheres pertaining to both ethnicity and national identity withimplications for each. The basic premise is that instead of being a final solution to aprotracted identity conflict, the PA symbolically reconceives the old MacedonianQuestion into a new form with an old essence. Thus, it does not resolve but rathercomplicates the identity security dilemma.
Keywords: MACEDONIA; GREECE; NAMING DISPUTE; ETHNICITY; NATIONALITY; PRESPA AGREEMENT